Use of alpaca and ichu manure for the production of briquettes as a source of heat energy in Arequipa - Palo Tejada, Juan Ernesto (2021)
In this work, tests were carried out to determine the calorific power of briquettes of alpaca and ichu manure and binder; the proportion of the mixture is 80% alpaca manure, 18% ichu, 2% lime and water in proportion to the manure. The results show the maximum temperature reached by the briquette under study is 500 ° C measured with an infrared thermometer and estimated calorific power for these briquettes 4318.18 cal / g. Due to the results obtained, the resulting briquettes can be used as an alternative and economical fuel that is also friendly to the environment. Alpaca manure at 4000 meters above sea level is not used as fertilizer for agriculture in the town of San Antonio de Chuca-Imata.